USE OF ULTRASONIC ENERGY IN REACTIVE DYEING OF CELLULOSIC FABRICS - (:unkn) unknown (SOC DYERS AND COLOURISTS PERKIN HOUSE, 1995)
The use of ultrasonic energy in dyeing cotton fabrics with monochlorotriazine and vinylsulphone reactive dyes has been studied spectrophotometrically. The dyeings carried out conventionally and by the use of ultrasonic techniques were compared in terms of percentage exhaustion, total amount of dye transferred to the washing bath after dyeing, fastness properties and colour values of the dyed materials. Overall results have shown that the use of ultrasound in reactive dyeing of cellulosic fabrics can result in energy savings, less water consumption, increased depth of colour and better process conditions.